The arts of citizenship in African cities : infrastructures and spaces of belonging - Diouf, Mamadou; Fredericks, Rosalind (Africa connects., 2014)
"Building upon a growing literature that resists the pathologizing effects of developmentalist and comparative framings, this fascinating collection of case studies pushes the frontiers of scholarship on African urbanism through detailed and nuanced ethnographic analyses of life in a diverse set of cities across the continent. These contributions explore a range of innovative institutions, discourses, and material practices through which claims to citizenship are enacted and contested by a diverse array of actors. They treat cities as sites of experimentation, privileging the ordinary, daily, under-the-radar negotiations through which emergent reconfigurations of citizenship are being continually forged. In doing so, they provide a more culturally informed perspective on African politics and society"--